Quality Educational Planning and Senior Secondary Education Goal Attainment in Ilorin Metropolis, Kwara State - Isiaka, B. Akanmu; Abdullateef, A. Adedayo; Oyedeji, N. Bisi (Kashere Journal of Education, 2022)
This study determined the relationship between quality educational planning and senior secondary education goal attainment in Ilorin metropolis, Kwara State. The study adopted a descriptive design of correlation type while its population comprised all the 3594 teachers across the public secondary schools in Ilorin metropolis. Simple random sampling technique was used to select 346 teachers in the metropolis. An adapted questionnaire titled “Quality Educational Planning Questionnaire” (QEPQ) and “Secondary Education Goal Attainment Proforma” (SEGAP) were used to collect data. Descriptive statistics of frequency count and percentage was used to answer the research questions while inferential statistics of Pearson product-moment correlation statistics was used to test the hypotheses at 0.05 level of significant. The findings of the study revealed that quality educational planning has a significant relationship with secondary education goal attainment in Ilorin metropolis, Kwara State. It was recommended that adequate classrooms and instructional facilities should continue to be adequately planned in order to keep the tempo of academic performance and enhance the level of senior secondary education goal attainment in Kwara State.